Larva of Halesus nurag Malicky 1974 (Trichoptera: Limnephilidae) and diagnostic key for the limnephilid larvae of Sardinia - Waringer, Johann; Malicky, Hans (Zootaxa, 2018)
This paper gives a description of the hitherto unknown larva of Halesus nurag Malicky 1974 (Trichoptera: Limnephilidae). Information on the morphology of the larva is given, and the most important diagnostic features are figured. In the context of the European Halesus species, the larva of H. nurag is morphologically close to H. appenninus Moretti & Spinelli Batta 1979, H. digitatus (Schrank 1781), H. radiatus (Curtis 1834), and H. tessellatus (Rambur 1842). This new morphological dataset was used for providing a key to the Sardinian limnephilid larvae. In this context, H. nurag can be separated from the other Sardinian species with single-filament gills described so far by chaetotaxonomical characters, mandible morphology, and details of the lateral protuberance of abdominal segment I.